2021
DOI: 10.1007/s12010-021-03660-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome Mining of Three Plant Growth-Promoting Bacillus Species from Maize Rhizosphere

Abstract: Bacillus species genomes are rich in plant growth-promoting genetic elements. Bacillus subtilis and Bacillus velezensis are important plant growth promoters; hence, to further improve their abilities, the genetic elements responsible for these traits were characterized and reported. Genetic elements reported include those of auxin, nitrogen fixation, siderophore production, iron acquisition, volatile organic compounds, and antibiotics. Furthermore, the presence of phages and antibiotic-resistant genes in the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 56 publications
2
9
0
4
Order By: Relevance
“…In plant development, the most crucial stage that affects yield is the flowering and pod-filling stage; hence, highly correlated bacteria taxa in this stage can be selected as effective biomarkers for improving crop yield in BGN ( Figure 3 ). Several studies have suggested that rhizosphere bacteria can improve nutrient availability for plant growth ( Babalola et al, 2019 ; Olanrewaju and Babalola, 2019a ; Olanrewaju et al, 2021a ). Due to the increase in diversity and correlation network pattern at the pod-filling and maturation stages, we can conclude that bacteria may play a more important ecological role at these stages than at the other growth stages.…”
Section: Discussionmentioning
confidence: 99%
“…In plant development, the most crucial stage that affects yield is the flowering and pod-filling stage; hence, highly correlated bacteria taxa in this stage can be selected as effective biomarkers for improving crop yield in BGN ( Figure 3 ). Several studies have suggested that rhizosphere bacteria can improve nutrient availability for plant growth ( Babalola et al, 2019 ; Olanrewaju and Babalola, 2019a ; Olanrewaju et al, 2021a ). Due to the increase in diversity and correlation network pattern at the pod-filling and maturation stages, we can conclude that bacteria may play a more important ecological role at these stages than at the other growth stages.…”
Section: Discussionmentioning
confidence: 99%
“…As an example of a pangenome study applied to rhizosphere bacteria, Olanrewaju et al [ 39 ], analyzed and compared the genomes of 10 PGPB belonging to the Bacillus genus, five strains were identified as B. subtilis and the other five as B. velezensis . Overall, the pangenome involved 777 core genes, with Bacillus subtilis strain BSA29 having the lowest amount of accessory and unique genes, and Bacillus subtilis R31 having the highest number of accessory and unique genes.…”
Section: Techniques To Study Plant-pgpb Interactionsmentioning
confidence: 99%
“…PGPR grows in/on/or around root plant tissue and enhances plant growth, increases yield, protects plants against pathogens, and/or reduces biotic and abiotic stress ( Trivedi et al, 2020 ; Ojuederie et al, 2021 ; Olanrewaju et al, 2021a ). Growth promotion can be achieved directly by the interaction between the microbe and the host, as well as indirectly, due to antagonistic activities against plant pathogens.…”
Section: Bambara Groundnut–bacterial Interactionsmentioning
confidence: 99%
“…Beneficial effects [such as biotic and abiotic stress tolerance ( Etesami and Maheshwari, 2018 ; Fazeli-Nasab and Sayyed, 2019 ; Ojuederie et al, 2019 ; Goswami and Suresh, 2020 ), increasing nutrient uptake ( Dhawi et al, 2015 ; Turan et al, 2016 ; Olanrewaju et al, 2017 ; Abdiev et al, 2019 ), pathogen control ( Olanrewaju and Babalola, 2019a , b ; Castaldi et al, 2021 ; Dave et al, 2021 ), and growth promotion ( Ajilogba et al, 2017 ; Valetti et al, 2018 ; Hakim et al, 2021 ; Olanrewaju et al, 2021a )] of bacterial on various plant hosts are well researched and very much understood. Ability to control and select for beneficial bacteria would proffer an avenue to improve these traits.…”
Section: Potential Of Genomics and Beneficial Microbes In Bgn Productionmentioning
confidence: 99%